From perception to practice: Pre-service teachers' development of ethnomathematics-based learning tools in Indonesia - Utami, Niken Wahyu; Sagita, Laela (Edelweiss Applied Science and Technology, 2025)
This research examines the correlation between pre-service mathematics teachers' perceptions of ethnomathematics-based instructional design and the quality of educational tools they produce during a university course. Employing a mixed-methods explanatory sequential design, quantitative data were gathered from 22 participants through a perception questionnaire utilizing a Likert scale. Descriptive statistics indicated generally positive perceptions, with a mean score of 42.36 and a standard deviation of 4.07, reflecting low variability among responses. Additionally, the final project assessments demonstrated moderately high performance, with a mean score of 37.77 and a standard deviation of 3.96. Qualitative analysis of lesson modules and student worksheets—evaluated via a rubric emphasizing cultural integration, mathematical coherence, and pedagogical quality—revealed diverse levels of success in incorporating local cultural elements into mathematics instruction. While many projects showcased innovative applications of ethnomathematical concepts, notable gaps persisted in aligning cultural contexts with explicit mathematical learning objectives and maintaining systematic lesson progression. The findings suggest that although pre-service teachers generally hold positive perceptions of ethnomathematics-based teaching design, these attitudes do not consistently translate into the development of high-quality, culturally embedded instructional materials. This discrepancy underscores the necessity for structured design training and reflective practice within teacher education programs. Such initiatives are essential to convert favorable perceptions into pedagogically sound and culturally responsive teaching tools. The study contributes to the ongoing discourse on integrating ethnomathematics into teacher education curricula. It highlights the importance of targeted curriculum development in culturally diverse educational settings and offers specific implications for enhancing instructional design through comprehensive training and reflective practices. Implementing these strategies can facilitate the effective translation of positive perceptions into practical, culturally relevant pedagogical approaches, ultimately enriching mathematics education in diverse cultural contexts.